Distribution of Orchids with Different Rooting Systems in the Czech Republic - Zuzana Štípková; Spyros Tsiftsis; Pavel Kindlmann (Plants, 2021)
Understanding diversity patterns along altitudinal gradients and the effect of global change on abundance, distribution patterns and species survival are of the most discussed topics in biodiversity research. Here, we determined the associations of orchid species richness and the degree of their specialization to specific environmental conditions (expressed by species specialization index) with altitude in six floristic areas in the Czech Republic. We distinguished three basic trends in these relationships: linear, parabolic and cubic. We then determined whether these trends differ between three orchid groups classified by their rooting systems: rhizomatous, intermediate and tuberous. We used distributional data on 69 species and subspecies of terrestrial orchids recorded in the Czech Republic and interpolated them at 100-m intervals along an altitudinal gradient in each floristic area. The trends in both species richness and mean species specialization index differed between the six floristic areas within each of the three orchid groups studied. These patterns are probably strongly influenced by the orography of the country and the distribution of different habitats in the six floristic areas in the Czech Republic. We also found that the most widely distributed orchid group in the Czech Republic are the rhizomatous orchids, followed by intermediate and tuberous ones.